Meningkatkan Hasil Belajar Matematika Di Kelas IVB SDN Bantarkemang 6 Melalui Pendekatan Teaching At The Right Level (TARL) - Dasri, Nabila; Nurani, Cahyaningtyas Dewi; Anwar, Wawan Syahiril; Falah , Fadailal Akmaln (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The independent curriculum emphasizes freedom to learn according to one's potential. This results in teachers having difficulty in providing learning according to the diverse abilities of students. Apart from that, in learning mathematics there are still many students who have difficulty in multiplication and division. For this reason, researchers conducted research with the aim of finding out improvements in student learning outcomes using the TARL approach in class IV B mathematics learning at SDN Bantarkemang 6. This research used the Classroom Action Research (PTK) type. The research subjects used class IV B students at SDN Bantarkemang 6 Bogor City with a total of 25 students. The instruments used in this study were observation and tests. The results of the study showed that the increase in student learning outcomes was 32% from before the action was given and after the action was given. Before the action was given, the number of students who had achieved learning completion was 12 out of 25 students with a completion percentage of 48%, while the number of students who had not completed was 13 children with a percentage of 52%. After the action was carried out in cycle I, the number of students who had achieved completion was 17 (68%), while the number of students who had not completed was 8 (32%). In cycle II, the number of students who had achieved completion was 20 (80%), while the number of students who had not completed was 5 (20%).